Genome-wide association study of sepsis in extremely premature infants. Issue 5 (10th March 2017) - Srinivasan, Lakshmi; Page, Grier; Kirpalani, Haresh; Murray, Jeffrey C; Das, Abhik; Higgins, Rosemary D; Carlo, Waldemar A; Bell, Edward F; Goldberg, Ronald N; Schibler, Kurt; Sood, Beena G; Stevenson, David K; et al.
Abstract : Objective: To identify genetic variants associated with sepsis (early-onset and late-onset) using a genome-wide association (GWA) analysis in a cohort of extremely premature infants. Study design: Previously generated GWA data from the Neonatal Research Network's anonymised genomic database biorepository of extremely premature infants were used for this study. Sepsis was defined as culture-positive early-onset or late-onset sepsis or culture-proven meningitis. Genomic and whole-genome-amplified DNA was genotyped for 1.2 million single-nucleotide polymorphisms (SNPs); 91% of SNPs were successfully genotyped. We imputed 7.2 million additional SNPs. p Values and false discovery rates (FDRs) were calculated from multivariate logistic regression analysis adjusting for gender, gestational age and ancestry. Target statistical value was p<10 −5 . Secondary analyses assessed associations of SNPs with pathogen type. Pathway analyses were also run on primary and secondary end points. Results: Data from 757 extremely premature infants were included: 351 infants with sepsis and 406 infants without sepsis. No SNPs reached genome-wide significance levels (5×10 −8 ); two SNPs in proximity to FOXC2 and FOXL1 genes achieved target levels of significance. In secondary analyses, SNPs for ELMO1, IRAK2 (Gram-positive sepsis), RALA, IMMP2L (Gram-negative sepsis) and PIEZO2 (fungal sepsis) met target significance levels. Pathways associated with sepsis and Gram-negative sepsis included gap junctions, fibroblast growth factor receptors, regulators of cell division and interleukin-1-associated receptor kinase 2 (p values<0.001 and FDR<20%). Conclusions: No SNPs met genome-wide significance in this cohort of extremely low birthweight infants; however, areas of potential association and pathways meriting further study were identified.